Organ support after death by neurologic criteria: Results of a survey of US neurologists. (23rd August 2016) - Lewis, Ariane; Adams, Nellie; Varelas, Panayiotis; Greer, David; Caplan, Arthur
Abstract : Objective: We sought to evaluate how neurologists approach situations in which families request prolonged organ support after declaration of death by neurologic criteria (DNC). Methods: We surveyed 938 members of the American Academy of Neurology (AAN) who treat critically ill patients, including 50% who practice in states with accommodation exceptions (states that require religious or moral beliefs to be taken into consideration when declaring death or discontinuing organ support: California, Illinois, New Jersey, New York), and 50% who practice in nonaccommodation states. Results: The survey was completed by 201/938 individuals (21% response rate), 96 of whom were from accommodation states and 105 of whom were from nonaccommodation states. Both groups reported encountering situations in which families requested continuation of organ support after DNC (48% from accommodation states and 46% from nonaccommodation states). In a hypothetical scenario where a request is made to continue organ support after DNC (outside of organ donation), 48% of respondents indicated they would continue support due to fear of litigation. In reply to an open-ended question, respondents requested that the AAN generate guidelines and advocate to codify laws regarding organ support after DNC, and to improve public and physician education on DNC. Conclusions: Our findings suggest that it is relatively common for neurologists who treat critically ill patients to encounter families who object to discontinuation of organ support after DNC at some point during their career. It would be beneficial for physicians, families, and society to rely on clear medicolegal guidelines on management of this situation.